Ovarian Sertoli–Leydig cell tumours: A systematic review of relapsed cases. (August 2021) - Nef, James; Huber, Daniela Emanuela
Highlights: Sertoli–Leydig cell tumour (SLCT) relapses occur early after the initial diagnosis and have a poor prognosis. The majority of SLCT relapses are located in the abdominopelvic region. Contralateral ovarian SLCT events (metachronous or recurrent) occur more frequently in paediatric cases. Paediatric cases and cases at stage I (Ia–Ic) at initial diagnosis have a better 5-year survival rate at relapse. Radical surgery appears to have a better 5-year survival rate, but the results are not significant. Multi-modal treatment with surgery and chemotherapy appears to be the best approach. Abstract: Objective: To synthesize the evidence on Sertoli–Leydig cell tumour (SLCT) relapses, and identify the clinicopathological characteristics and prognosis of patients with recurrent SLCT. Methods: A literature search was undertaken of all published cases of SLCT relapse found in PubMed, Embase and Web of Science databases between January 1998 and January 2021. All articles in English reporting at least one case of SLCT relapse and mentioning the relapse location or the follow-up data were included. All reported data on relapsed cases were extracted. Student's t -test and Chi-squared test were used for the descriptive analysis, and the Kaplan-Meier statistical method was applied for survival analysis. Results: Eighty-five patients from 33 articles were included in this review. The median age was 20 years (range 3–76 years) with a median time to relapse of 14 months (range 1–168 months). Forty-eight percent (36/75) of relapses were local and 52% (39/75) were distant. In the subgroup of conservative primary surgery, contralateral ovarian SLCT events (metachronous or recurrent) were more frequent in the paediatric population than in the adult population (58.3 vs 18.2%; p  = 0.005). Eleven cases had multiple relapses. Twenty-one percent (12/57) of cases were treated with conservative surgery after recurrence, and 64.9% (37/57) of cases were treated with radical surgery which tends to have a better 2-year survival rate (78.5% vs 61.0%; p  = 0.177). Overall median survival was 48 months after recurrence (95% confidence interval ±21.0 months) with overall 5-year survival of 38.9%. The mean survival time was significantly higher for patients diagnosed at an early stage (I and II) compared with patients diagnosed at an advanced stage ( p  = 0.003). Discussion: The results showed that SLCT relapses have a poor prognosis and occur mainly in young patients, soon after the initial diagnosis. The majority of SLCT relapses are located in the abdominopelvic region. Contralateral ovarian SLCT events (metachronous or recurrent) occurred more frequently in paediatric cases. Multi-modal treatment with surgery and chemotherapy appears to be the best approach. The best chemotherapeutic regimen has yet to be defined.